Islamic Legal Reform on Child Marriage in Southeast Asian Muslim Countries: A Systematic Literature Review - Amri Saputra (PT Taskuliah Edukasi Indonesia, 2026)
Child marriage remains a persistent social and legal challenge in Southeast Asian countries, particularly in Indonesia and Malaysia. Although international human rights conventions and national legal reforms have been implemented, the practice of child marriage continues to occur; in some cases, it is even encouraged through religious interpretations, customs, and cultural traditions. This study aims to analyze the dimensions, driving factors, legal framework, and direction of child marriage reform within Southeast Asian Muslim communities, whilst mapping out the research agenda that needs to be developed in the future. This study employs a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 guidelines, synthesizing 34 peer-reviewed scientific articles from 82 Scopus-indexed documents. The findings identified five main thematic clusters, namely: (1) legal dimensions and Islamic doctrine; (2) state law and institutional responses; (3) social, cultural, and economic determinants; (4) feminist and community-based resistance; and (5) digital influences and contemporary dynamics. The research findings reveal an ongoing tension between Islamic jurisprudence (fiqh), customary law (adat), and international standards on children’s rights. This research concludes that there is a need for policy interventions that are sensitive to children’s rights whilst being rooted in the local cultural context, and for a reorientation of Islamic legal reasoning that prioritizes children’s welfare and protection. Directions for future research recommend the development of longitudinal studies on the individual experiences of child marriage, comparative studies, and research into the role of the digital sphere in reshaping marriage norms amongst young Muslims. [Perkawinan anak masih menjadi tantangan sosial dan hukum yang persisten di negara-negara Asia Tenggara, khususnya di Indonesia dan Malaysia. Meskipun konvensi hak asasi manusia internasional dan reformasi hukum nasional telah diterapkan, praktik perkawinan usia anak masih tetap terjadi bahkan dalam beberapa kasus didorong memalui melalui interpretasi keagamaan, adat istiadat, dan budaya. Penelitian ini bertujuan menganalisis dimensi, faktor pendorong, kerangka hukum, serta arah reformasi perkawinan anak di kalangan komunitas Muslim Asia Tenggara, sekaligus memetakan agenda penelitian yang perlu dikembangkan ke depan. Kajian ini menggunakan pendekatan tinjauan literatur sistematis (Systematic Literature Review/SLR) yang dipandu oleh pedoman PRISMA 2020, dengan mensintesis 34 artikel ilmiah peer-reviewed dari 82 dokumen terindeks Scopus. Hasil kajian mengidentifikasi lima klaster tematik utama, yaitu: (1) dimensi hukum dan doktrin Islam; (2) hukum negara dan respons kelembagaan; (3) determinan sosial, budaya, dan ekonomi; (4) resistensi feminis dan berbasis komunitas; serta (5) pengaruh digital dan dinamika kontemporer. Temuan penelitian menunjukkan adanya ketegangan yang terus berlangsung antara yurisprudensi Islam (fiqh), hukum adat (adat), dan standar internasional mengenai hak-hak anak. Penelitian ini menyimpulkan perlunya intervensi kebijakan yang sensitif terhadap hak anak sekaligus berakar pada konteks budaya lokal dan reorientasi penalaran hukum Islam dengan menempatkan kesejahteraan dan perlindungan anak sebagai prioritas. Arah penelitian mendatang merekomendasikan pengembangan studi longitudinal terhadap pengalaman individu perkawinan anak, studi komparatif, serta kajian mengenai peran ruang digital dalam membentuk ulang norma perkawinan di kalangan generasi muda Muslim].